Pengaruh Penggunan E-Commerce, Financial Technology, Media Sosial Dan Modal Terhadap Pendapatan UMKM Kota Padang - Ferliansyah; Riani Sukma Wijaya (CV. ITTC INDONESIA, 2024)
Intense competition necessitates MSME owners to utilize existing technologies to remain competitive. Despite the advanced state of technology, much of MSMEs in Indonesian haven’t used it yet for bussiness sustainability. This study aims to know how much effect of e-commerce, financial technology, social media and capital has on MSME income in Padang City. The population in this study is the owner of MSMEs in Padang City specifically in Koto Tangah with nonprobability sampling method. The result of this study prove that e-commerce has no effect on MSME income. Meanwhile, financial technology, social media and capital has effect on MSMEs income. However, the use of e-commerce, financial technology, social media and capital has a simultaneous effect on MSMEs income. This study conducted in only Koto Tangah district area. For the next study, expected to conduct more extensive area.